Analyzing competing demands in organizations: A systematic comparison - Medhanie Gaim; Nils Wåhlin; Miguel Pina e Cunha; Stewart Clegg (Journal of Organization Design, 2018)
Organizational scholars have shown increasing interest in the ways in which managers enact and respond to competing demands and the tensions they prompt as constitutive elements of their organizations. There is now a proliferation of conceptualizations of such competing demands that can be somewhat confusing. We will enhance conceptual clarity by identifying seven constitutive empirical characteristics of competing demands: these consist of the existence of dyadic relations, contradiction, interrelatedness, complementarity, compatibility, simultaneity, and the existence of push-pull forces. We construct a comparative classification of competing demands using these characteristics as our distinguishing features. The result is a more nuanced understanding of how managers approach competing demands that can help scholars to minimize arbitrariness, interpret results, and compare contributions in the area in a much-needed step toward understanding and designing organizations.
Keywords: 650; Competing demands; Organizational contradictions; Organizational design; Organizational tensions; Paradox theory